Preserving Hope in the "Duty to Protect": Counselling Clients with HIV or AIDS - Wong-Wylie, Gina (Canadian Journal of Counselling and Psychotherapy, 2007)
Psychologists may struggle with what to do when counselling recalcitrant HIV-positive clients who refuse to disclose to third parties at risk. This paper revisits the legal and ethical quagmire that pits "dangerous patient exception" against client confidentiality rights. With the notion that hope leads to more ethical behavior, this paper further elucidates the significance of maintaining client hope in the face of a legal "duty to protect". A 'duty to maintain hope', which may ultimately minimize the spread of HIV in society by inviting client's social responsibility, is proposed. A four-level guide is offered to assist Canadian psychologists in this endeavor. Future research directions are suggested.